The Effect of Concentration and Exposure Time Acyclovir for Elimination Sugarcane Mosaic Virus (SCMV) on The Apical Bud Culture of Sugarcane PS 881 - Maisaro, Maisaro; Sugiharto, Bambang; Dewanti, Parawita (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
SCMV (Sugarcane Mosaik Virus) is sugarcane crop disease resulting in chlorosis in leaves with the formation of the colors yellow and green intermittents. Based on survey information obtained that the air observation of all varieties of sugarcane was already stricken with the virus SCMV. Even the most formidable attack is on PS881 varieties with the intensity of the attacks reached 80%, so that it is estimated will lose up to 40% of the harvest. The sugarcane is virus free can be obtained via organogenesis in tissue culture method directly on the apical meristem, somatic embryogenesis at, and also with the addition of khemoterapeutan (acyclovir).The workings of the khemoterapi materials are the chemotherapi will interfere with replication and synthesis of genetic material of the virus but also cause the same effect against the mechanism of synthesis of nuklet acid on plants hosts. This research aims to find the best concentration and exposure time the most good in eliminating viruses SCMV in the apical bud culture of sugarcane PS881, using the antiviral acyclovir in conditions of invitro, so that the resulting plant will be virus free. The methods used to detect the presence of the virus by using the two ways, the first is by serology test through the protein content of the virus / checking nucleic acid virus with ELISA and the second is by RT-PCR. The results of the analysis showed that the interaction between the concentration of chemotherapy and exposure time produces the best treatment in eliminating the virus was . treatment with acyclovirc oncentration of 20 ppm and exposure time of 5 weeks.